Experimental and theoretical investigation of conformational states and noncovalent interactions in crystalline sulfonamides with a methoxyphenyl moiety. Issue 35 (11th August 2021) - Kowalik, Mateusz; Brzeski, Jakub; Gawrońska, Małgorzata; Kazimierczuk, Katarzyna; Makowski, Mariusz
Abstract : The conformational and noncovalent interaction properties of sulfonamides with a methoxyphenyl moiety were examined by both experimental and theoretical methods. Abstract : Four sulfonamide derivatives with a methoxyphenyl moiety, namely N -4-[(2-methoxyphenyl)sulfamoyl]phenylacetamide (1a ), N -4-[(3-methoxyphenyl)sulfamoyl]phenylacetamide (1b ), 4-amino- N -(2-methoxyphenyl)benzenesulfonamide (2a ) and 4-amino- N -(3-methoxyphenyl)benzenesulfonamide (2b ), have been synthesized and characterized physiochemically by CHNS, MS, FT-IR, 1 H NMR, 13 C NMR, PXRD and TG methods. Crystal structures were determined by SC-XRD and their conformational and noncovalent interaction properties were examined by both experimental and theoretical (HS, MEPS, NBO, dimerization energy, QTAIM) methods. The conformational flexibility of the bridge connecting two phenyl rings was studied and minimum-energy conformations were theoretically found. The packing architecture and hydrogen bond networks were described by graph set notation. Hirshfeld surface analysis revealed regions of stronger contacts and allowed us to indicate the relative contributions of different noncovalent contacts in the crystal packing. MEPS calculations helped to distinguish the electron rich and electron poor regions and to find the best H-bond donors and acceptors. The use of the QTAIM method enabled us to explain the influence of functional groups and molecular arrangement on the strength of noncovalent interactions in the crystals and overall packing efficiency.